A Review of the Current Regulatory Framework for Supersonic Civil Aircraft: Noise and Emissions Regulations - Thomas Rötger; Chris Eyers; Roberta Fusaro (Aerospace, 2023)
The request for faster and greener civil aviation is urging the worldwide scientific community and aerospace industry to develop a new generation of supersonic aircraft, which are expected to be environmentally sustainable, and to guarantee a high level of protection for citizens. The availability of novel propulsive technologies, together with the development of new civil supersonic passenger aircraft configurations and missions, is pushing international authorities to update the regulatory framework to limit nuisances on the ground and the contribution to climate change. Existing ICAO noise and emissions standards are outdated as they were developed in the 1970s and tailored to Concorde, the only SST that has ever operated in Western airspace. This article provides (i) a comprehensive review of current environmental regulations for SST, encompassing noise and pollutant emissions near airports (LTO cycle) as well as CO2 emissions and sonic booms, and (ii) updated information about the ongoing rulemaking activities by ICAO, FAA and EASA. This review clearly highlights the following findings: (i) the need to revise current rules to better fit future SST design, operations and technologies; (ii) the need to introduce new regulations to cover additional aspects, including stratospheric water vapour emissions and ozone depletion; and (iii) the need to support regulatory activities with solid technical bases, fostering cooperation with academia, research centres and industry in R&D projects. Eventually, a practical example of how SST rulemaking activities are supported by the collaborative research H2020 MORE&LESS is reported.